Structural changes in silicate melt: A record from high-field strength elements in the Himalayan Cenozoic leucogranites - Gao, Li-E.; Zeng, Lingsen; Yan, Lilong; Zhao, Linghao; Wang, Yaying (Frontiers in Earth Science, 2023)
Most Himalayan Cenozoic leucogranites are peraluminous magmas that have experienced various degrees of fractional crystallization. These leucogranites are characterized by relatively high degrees of heterogeneity in their elemental compositions. As the melt’s Zr/Hf ratio passes ∼20, there is an apparent change from positive to negative in the correlation between Zr (or Hf) and Zr/Hf ratio. As Nb/Ta ratio passes ∼5, Nb first decreases and then increases, but Ta first slowly increases and then drastically increases. Such systematic geochemical variations are related to changes in the dissolution behavior of key accessory phases, which are the consequence of silicate melt structural changes associated with fractional crystallization and. As a granitic magma evolves, changes in the melt structure as shown by changes in the compositional parameters (e.g., NBO/T, A/CNK, and M/F) as well as in Zr/Hf and Nb/Ta ratios. When the melt’s Zr/Hf and Nb/Ta ratio passes 20 and 5, respectively, NBO/T, M/F, and A/CNK first decrease and then increase; A/NK and C/NK first decrease and then become nearly constant; Na/K first becomes nearly constant and then increases. Moreover, a substantial change in the melt structure leads to a decrease in granitic viscosity, which in turn fractional crystallization of the granitic melts. Finally, such changes result in the mineralization of economically relevant rare elements in the Himalayan Cenozoic leucogranites.